Analysis of the interaction of Ag and ZnO nanoparticles in Phaseolus vulgaris - Savassa, Susilaine Maira (2019)
Nanoecotoxicology is a growing field of science driven by the extensive use of nanomaterials in commercial products and agriculture. Their use in agriculture is to become a reality through fertilizers and pesticides. On the other hand, little is known about possible collateral effects that of nanomaterials and therefore they may pose a threat to human health and the environment. To shed light on these topics, one must better understand the mechanisms of interaction between nanoparticles (NP) and living beings. Seed treatment is a common practice that provides micronutrients and protection. This study investigated the effects of ZnO and Ag NP on the germination of Phaseolus vulgaris seeds and the interaction (uptake and biotransformation) with the seed coat. Zinc-based nanoparticles were chosen because it is a plant micronutrient, whilst Ag ones present antimicrobial activity. The common bean seed treatments and synchrotron analysis were performed at the ID21 beamline in ESRF, CENA-USP and XRF beamline in LNLS. The bean seed coat presents three different layers, which are one of the objects of this study. The seeds were exposed to Ag2S NP, Ag metallic NP, ZnO NP, AgNO3 and ZnSO4 in different concentrations (Ag 100 and 1000 mg L-1 while Zn 100, 1000 and 5000 mg L-1). After 5 days of post-treatment and germination, seed coats were recovered, sectioned and investigated by FTIR, -XRF and -XANES. -XRF analysis showed that most of the NP treatments remained trapped in the seed coat, while -XANES unraveled that depending on the composition of pristine materials they can be biotransformed. Finally, FTIR pointed out that the proportion of organic functional groups present in the seed tissue were modified due to the presence of NP